ANALISIS PENGARUH KARAKTERISTIK PEKERJAAN DAN KOMPETENSI TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA (Studi Pada SMP Muhammadiyah Se Kabupaten Pati) - Hartiwi, 12.52.02.0225 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze the effect of job characteristics and competence of the teachers performance with the mediation of job satisfaction in SMP Muhammadiyah of Pati regency. Sampling was done by census method so that all teachers who work in SMP Muhammadiyah of Pati regency, amounting to 99 people as respondents. Data collected by distributing questionnaires to the respondents and all questionnaires were returned with complete. Mechanical testing data used include test validity by factor analysis, reliability testing with Cronbachâs alpha formula, multiple regression analysis, and the significance test, the coefficient of determination to prove the truth of the research hypothesis and test mediation. The results showed that; job characteristics and competencies of teachers has positive and significant impact on job satisfaction, job characteristics and competencies of teachers has positive and significant impact on teacher performance, job satisfaction is not able to mediate the effect of job characteristics on teacher performance, and job satisfaction is able to mediate the effect of the influence on the performance of teachers competence.Keywords: Job Characteristics, Competencies, Job Satisfaction, Teacher Performance